Ethical Identity Index and Financial Performance of Islamic Banks in Asia - sumiyati sumiyati; Vebtasvili Vebtasvili (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2021)
This study is a follow-up study conducted by Zaki et al. (2014), who explored Islamic banks' ethical identity with financial performance. This study aims to identify the identity of Islamic banks in Asia against Shari'ah law and examine the relationship between EII and financial performance. The data used are financial data from 7 Islamic banks in Asia in 2016-2019. The study results show that the higher the EII value, the higher the Islamic bank supervision of sharia. Then the researcher describes the relationship between EII and financial performance as measured by using Return On Assets. The result is that there is no relationship between EII and financial performance.